Radiation dose homogeneity and critical organs in radiotherapy treatment of prostate cancer - Khairi, Y.; Omer, H.; Sulieman, A.; Deiab, N.; Mokhtar, Maha H.; Abolaban, Fouad A.; Alkhorayef, M.; Bradley, D.A. * (Elsevier, 2021)
Present study compares two different 3D radiotherapy techniques: three-dimensional conformal radiotherapy (3D-CRT) and 3D external-beam radiation dose fields from computerized treatment plans, produced for 30 prostate cancer patients. All of the patients were the subject of treatment at the National Cancer Institute in Egypt. Evaluation was made of dose homogeneity within the target volume and the dose to critical organs (organs at risk, OAR). The plans were based on CT scans, all for cases of localized prostate cancer (all stage T2N0M0), with the CT scans transferred to the treatment planning systems. Comparison of the two different 3D radiation techniques was made in terms of isodose distributions and dose-volume histograms. The percentage of the planning target volume receiving 95% (V95) and 107% (V107) of the prescribed dose were obtained. For the 3D-CRT technique, the mean values for these were respectively 90.6% and 5.7% while for the other 3D technique they were 94.9% and 3.8%. In examining the dose received by the OAR, use of the 3D-CRT technique was found to provide the preferred dose distribution, with much greater sparing of the bladder, rectum and head of both femora. For the rectum the mean V70, V75 and D95 values (the latter referring to doses to 95% of the treatment volume) for the 3D-CRT technique were 35.5%, 32.2% and 34% while for the other 3D technique these were 8.4%, 0.2% and 12% respectively. For the bladder, the mean V40 and V65 values obtained using the 3D-CRT technique were 80.8% and 74.9% while for the alternative 3D technique they were 20.4% and 17% respectively. Thus for the particular cohort, the 3D-CRT technique provided superior target coverage and reduction of dose to the OAR.